Development of an approach to incorporate proportional hazard modelling into a risk-based inspection methodology for an optimal inspection policy - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2024)
Thesis (PhD (Mechanics))--University of Pretoria, 2024.